Pollutants, human health, and the environment : a risk based approach - Plant, Jane A.; Voulvoulis, Nikolaos; Ragnarsdottir, Kristin Vala, 1954- (Chichester, West Sussex, U.K. ; Hoboken, N.J. : Wiley-Blackwell, 2012)
Pollutants, the Environment and Human Health is a comprehensive, up-to-date overview of environmental pollutants that are of current concern to human health. Clearly structured throughout, the main body of the book is divided by pollutant type with a chapter devoted to each group of pollutants. Each chapter will follow a similar format to facilitate comparison and discussion. For each pollutant, the authors describe the sources, pathways, environmental fate and sinks as well as known toxicological effects. Importantly the second chapter on heavy metals and other inorganic substances will deal.
POLLUTANTS, HUMAN HEALTH AND THE ENVIRONMENT: A RISK BASED APPROACH; Contents; Forewords; Tribute; The Editors; Contributors; Acknowledgements; Introduction; 1 The scientific appraisal of hazardous substances in the environment; 1.1 Introduction; 1.2 Fundamental concepts of toxicology; 1.3 Some notions of environmental epidemiology; 1.4 Scientific evidence and the precautionary principle; 1.5 Uncertainty and controversy: the endocrine disruption example; 1.6 Concluding remarks; References; 2 Regulatory systems and guidelines for the management of risk; 2.1 Introduction.
Includes bibliographical references and index.
Print version record.
Keywords: Pollution; Pollution -- Health aspects; Nature -- Effect of human beings on; Engineering; Environmental engineering; Environmental Studies; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; Nature -- Effect of human beings on; Pollution; Pollution -- Health aspects; Electronic books